الوِلاية في الإسلام كأساس للاَّمركزية الإدارية من خلافة عمر إلى العهد الأموي. (Revue El-Wahat pour les Recherches et les Etudes, 2020)
The study dealt with the "Wilaya" as a region of the Islamic State in the era of Omar ibn al-Khattab and was independent from it and the independence that characterized it in many political, financial, social and organizational aspects. This was reflected in the administrative decentralization whereby many powers were delegated to the governors. And  solve the problems of their flock without reference to the Caliph Hence, the study focused on the authorities and the financial, administrative and organizational authorities, which is supervised by the Caliph, and he does not appoint the Caliph, considering that he met, integrity and piety, and isolates him if he fails to conduct his affairs and asks about it. The study also dealt with the tasks and powers granted to the Governor and the other Which remained focused on the ruler because of the importance of the utmost or the nature of the special, while addressing the most important mandates that emerged in this golden period, which reflected the images of modern administrative decentralization. Key words- Wilaya, Administrative decentralization, Administrative organization, the succession of Omar, Islam.